Case report: Acute liver failure in children and the human herpes virus 6-? A factor in the recent epidemic - Warner, Suz; Brown, Rachel M.; Reynolds, Gary M.; Stamataki, Zania; Kelly, Deirdre A. (Frontiers in Pediatrics, 2023)
The 2022 worldwide epidemic of acute hepatitis and liver failure of unknown aetiology in young children has led to a focus on unusual causes for childhood acute hepatitis. In the UK epidemic, human herpes virus subtype 6B (HHV-6B) has been detected along with adenovirus subtype-41F in severely affected children, especially in those requiring liver transplantation (LT). The lifting of COVID lock-down measures has coincided with the rise in common childhood infections with a higher than expected rate of systemic complications. This is hypothesised to be related to the lifting of COVID lock-down measures in which young children are suddenly exposed to common childhood infections from which they were protected during long periods of social isolation. Primary HHV-6 infection is one such common infection and most children are usually infected by age 2 years. Classically known as Roseola infantum due to the appearance of a widespread erythematous rash on fever subsidence (exanthema subitem), it is the infection frequently linked to febrile convulsions. However, the more serious complications of hepatitis and liver failure are rare except in immunocompromised individuals. The development of these complications can lead to significant morbidity and mortality. We report on the historic cases of three female infants who had suspected primary HHV-6B infection, acute hepatitis and rapid progression to acute liver failure (ALF). All required LT. Appearances of their native liver were identical to those described in children in the recent hepatitis epidemic. Deteriorating clinical trajectories of recurrent graft hepatitis and rejection-like episodes followed and all three succumbed to graft failure with HHV-6B detected posthumously in their liver allografts. Our case series and the serious complications observed with the recent rise in common childhood infections is a reminder that these routinely encountered pathogens can be deadly especially in the young immunologically untrained. We advocate for HHV-6 to be screened for routinely in children with acute hepatitis and the use of effective HHV-6 anti-viral prophylaxis to prevent recurrence post-transplant.